Binocular Summation Is Intact in Intermittent Exotropia After Surgery - Xu, Meiping; Chen, Yiya; Peng, Yiyi; He, Zhifen; Jiang, Jun; Yu, Xinping; Hou, Fang; Zhou, Jiawei; Qu, Jia (Frontiers in Medicine, 2021)
Purpose: To determine binocular summation of surgically treated intermittent exotropia (IXT) patients by measuring the contrast threshold. Methods: We recruited 38 surgically treated IXT patients aged 8 to 24 years and 20 age-matched healthy controls. All participants had normal or corrected-to-normal visual acuity (Snellen ≥ 20/20) in both eyes. The IXT patients had undergone the surgery at least a year prior to the study. 21 of them obtained good alignment and 17 experienced a recurrence of exotropia. We measured the observers’ monocular and binocular contrast sensitivities (CS) at six spatial frequencies (1.5, 3, 6, 12, 18, 24 cycles/degree) as an index of visual information processing at the threshold level. Binocular summation was evaluated against a baseline model of simple probability summation based on the CS at each spatial frequency and the area under the log contrast sensitivity function (AULCSF). Results: The exo-deviation of IXTs with a good alignment was -6.38 ± 3.61 pd at 33cm and -5.14 ± 4.07 pd at 5m. For the patients with recurrence, it was -23.47 ± 5.53 pd and -21.12 ± 4.28 pd, respectively. There was no significant difference in the binocular summation ratio (BSR) between the surgically treated IXT patients, including those with good alignment and recurrence, and normal controls at each spatial frequency (F (2, 55) = 0.416, P = 0.662) and AULCSF (F (2, 55) = 0.469, P = 0.628). In addition, the BSR was not associated with stereopsis (r=-0.151, P=0.365). Conclusion: Our findings of normal contrast sensitivity binocular summation ratio in IXT after surgical treatment suggest that the ability of the visual cortex in processing binocular information is intact at the contrast threshold level.